Applications of nuclear magnetic resonance spectroscopy in organic chemistry - Jackman, Lloyd Miles; Sternhell, S. (International series of monographs on organic chemistry, 1969)
Application of Nuclear Magnetic Resonance Spectroscopy in Organic Chemistry, Second Edition covers the theoretical background necessary for the intelligent application of NMR spectroscopy to common problems encountered in organic chemistry. This book is composed of five parts, and begins with introduction to the theory and practice of nuclear magnetic resonance. The succeeding chapter deals with the theory of chemical effects in NMR spectroscopy. These topics are followed by a discussion on the application of chemical shift to organic compound analysis and the principles of the spin-spin coupl.